2022
DOI: 10.1021/acs.jproteome.2c00318
|View full text |Cite
|
Sign up to set email alerts
|

TMT-Based Comparative Peptidomics Analysis of Rice Seedlings under Salt Stress: An Accessible Method to Explore Plant Stress-Tolerance Processing

Abstract: Rice (Oryza sativa L.) is an important staple crop, particularly in Asia, and abiotic stress conditions easily reduce its yields. Salt stress is one of the critical factors affecting rice growth and yield. In this study, a tandem mass tag (TMT)-based comparative peptidomics analysis of rice seedlings under salt stress was conducted. Rice seedlings were exposed to 50 and 150 mM NaCl for 24 and 72 h, respectively, and the root and shoot tissues of different treatment groups were collected separately for peptidom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Rice drought and salt stress response-1 (OsDSSR1) peptide (Cui et al, 2018) and drought tolerance 11 (OsDT11) peptide (Li et al, 2017) have been indicated to be associated with stress tolerance. Peptidomics provides a powerful method to identify peptides with the potential functional roles in plants (Ma et al, 2022), and it is now being used for bioactive peptide and biomarker discovery (Agyei et al, 2018;Trindade et al, 2021). However, peptidomics study on the establishment of seed vigor is limitedly in tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…Rice drought and salt stress response-1 (OsDSSR1) peptide (Cui et al, 2018) and drought tolerance 11 (OsDT11) peptide (Li et al, 2017) have been indicated to be associated with stress tolerance. Peptidomics provides a powerful method to identify peptides with the potential functional roles in plants (Ma et al, 2022), and it is now being used for bioactive peptide and biomarker discovery (Agyei et al, 2018;Trindade et al, 2021). However, peptidomics study on the establishment of seed vigor is limitedly in tobacco.…”
Section: Introductionmentioning
confidence: 99%